ANTIBACTERIAL ACTIVITY TEST OF EXTRACT ETHANOL MANGO ARUM MANIS SKIN (Mangifera indica L) ON Methicillin Resistant Staphylococcus aureus (MRSA - -, Wulandari; Sulistyarini, Indah (Media Farmasi Indonesia, 2018)
Methicillin resistant Staphylococcus aureus (MRSA) is a strain of Staphylococcus aureus that has been resistant to the antibiotic activity of the β-lactam group, including the penicillinase-resistant penicillins (oxcacillin, methicillin, nafcillin, cloxacillin, dicloxacillin), cephalosporin and carbapenem. Therefore, it is necessary to consider the use of alternative antibiotics, especially through the utilization of Indonesian medicinal plants. One of them is the use of mango arum manis skin (Mangifera indica L). The skin of mango contains phenolic compounds, carotenoids, flavonoids and anthocyanins. This research aims to determine whether mango arum manis skin extract has the ability to inhibit the growth of MRSA bacteria. Mango cultivar arum manis skin extract is made by remacerationmethod with 70% ethanol solvent. Test of Antibacterial activity of mango arum manis skin extract was undertaken by diffusion method at 5%, 10%, 15%, 20%, 25% concentration with positive control of ciprofloxacin and negative control of dimethylsulfoxide (DMSO). The results showed that mango arum manis skin extract has the ability to inhibit the growth of MRSA bacteria.